Assessing Leadership Styles, Self-Efficacy, Job Satisfaction, and Organizational Commitment in Rural Administrative Officials Through Mixed-Methods and Quantitative Data Analysis - Aheruddin, Aheruddin; Eryanto, Henry; Sariwulan, Tuty (Bright Publisher, 2024)
This study explores the relationship between leadership styles, self-efficacy, job satisfaction, and organizational commitment among rural administrative officials on Sumbawa Island. Utilizing a mixed-methods approach, the research combines quantitative data from surveys and qualitative insights from interviews across four districts: Bima, Dompu, Sumbawa, and Sumbawa Barat. The findings indicate that transformational leadership significantly enhances organizational commitment, with Bima exhibiting the highest commitment scores (mean = 4.18), followed by Sumbawa (mean = 3.92). In contrast, transactional leadership, more common in Dompu, correlates with lower commitment (mean = 3.09). Self-efficacy also plays a crucial role, with higher scores associated with increased job satisfaction and commitment, particularly in Sumbawa (mean = 3.75) and Bima (mean = 3.38). Job satisfaction mediates the relationship between leadership styles and organizational commitment, underscoring its importance in fostering a dedicated workforce. The study reveals significant contextual differences, emphasizing the need for tailored leadership development programs that address specific socio-cultural and demographic factors. Key contributions include empirical evidence supporting transformational leadership in rural administration and the integration of self-efficacy into leadership theories. Recommendations for future research include longitudinal studies and multi-source assessments, while practical applications suggest focusing on transformational leadership training, enhancing self-efficacy, and improving job satisfaction through better working conditions and career advancement opportunities. By addressing these factors, rural administrations can enhance organizational commitment and improve governance outcomes, ultimately contributing to sustainable rural development.